Spregled pravne osebnosti v slovenski sodni praksi - Mayr, Vida (Pravni letopis, 2014)
Despite the fact that the institute disregard of legal personality ("lifting the corporate veil") was introduced in Slovene legislation more than twenty years ago, in the case law the creditors have seldom success by enacting this legal institute. In the past one of the reasons was the responsibility of the shareholders for liabilities of erased companies. The process situation of the creditors is difficult due to the information asymmetry and the burden of proof. This may change the recent case-law that, in some cases, exceptionally allows informative evidence. The position of creditors could also be facilitated by reversed burden of proof in proving the subjective element from the 4. Indent 8. Article Slovene Companies Act. Despite the interest of the creditors the disregard of legal personality has to remain the exception. The use of this in
Keywords: dolgovi; družbeniki; odgovornost; pravne osebe; spregled pravne osebnosti